2018
DOI: 10.1016/j.ijsu.2017.11.034
|View full text |Cite
|
Sign up to set email alerts
|

“Sports Ultrasound”, advantages, indications and limitations in upper and lower limbs musculoskeletal disorders. Review article

Abstract: Ultrasonography (US) is a safe and noninvasive imaging modality that is gaining popularity in different medical and surgical fields. Its introduction in musculoskeletal and sports medicine has taken this advanced subspecialty to a higher level. It has the advantage over other imaging techniques with regards to ease of use, availability, comfort and cost. Not to mention, in terms of safety profile, patients are not exposed to radiations, like in x-rays, and it can be performed on patients with metal or pacemake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 74 publications
0
20
1
2
Order By: Relevance
“…15,16 . However, the present study found that the ultrasound images of the lateral meniscus in the DLM group and the control group were all approximately inverted triangles, which maybe arise from the limitedly ultrasonic scanning on the depth of the knee joint space and incompletely display of DLM 7,18 .…”
Section: Validation Of Ultrasound Diagnostic Criterioncontrasting
confidence: 55%
See 4 more Smart Citations
“…15,16 . However, the present study found that the ultrasound images of the lateral meniscus in the DLM group and the control group were all approximately inverted triangles, which maybe arise from the limitedly ultrasonic scanning on the depth of the knee joint space and incompletely display of DLM 7,18 .…”
Section: Validation Of Ultrasound Diagnostic Criterioncontrasting
confidence: 55%
“…Magnetic resonance imaging (MRI) is the "gold standard" in imaging diagnosis of DLM with a clear diagnostic criterion and a high sensitivity (95%) and specificity (97%) 5 , but it has high costs and long examination times, and is contraindicated in patients with installed pacemakers, magnetic metal implanted, and claustrophobia 6,7 . Besides, MRI is difficult to perform in young children who may not remain motionless during the imaging study.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 3 more Smart Citations